Ethnosocilinguistic study on the language selection at imigrant Pendalungan communities in Gresik - Yanti, Putri Indah (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
ABSTRACT Â This paper is a study that examines the language code used by immigrant communities from the Tapal Kuda area, which is usually referred to as the Pendalungan group (the result of acculturation of Madurese and Javanese cultures who live and settle in the coastal area, in Roomo Pesisir Village, Gresik and their language patterns. This research is a qualitative research because it produces descriptive data in the form of written or spoken words from people and their observable behavior. The data collection techniques used are observation and interviews. At the data analysis stage, using ethnomethodological techniques in Ethnosociolinguistics. This study produced three language codes for the immigrant community in the Roomo Pesisir region, Gresik with details: 1) Indonesian; 2) Javanese (ngoko and krama); 3) Madurese (rough) language, and seven patterns of language selection in daily interactions by migrants from the Roomo Pesisir region, Gresik. The seven patterns of language selection are 1) everyday language in the family; 2) Language at school/workplace; 3) Language with fellow immigrants from the same area; 4) Language at the event (celebration, vaccine, recitation, etc.); 5) Language with parents; 6) Language based on ethnicity; 7) Language based on social status. The seven language patterns are the result of friction in the use of the three languages by speakers at the same time Keywords: Etnosiciolinguistic, Language Pattern, Imigrant Communities